2015
DOI: 10.1103/physrevb.92.205119
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Curie temperature enhancement in electron-doped EuO

Abstract: We present a comparative, theoretical study of the doping dependence of the critical temperature TC of the ferromagnetic insulator-metal transitions in Gd-doped and O-deficient EuO, respectively. The strong TC enhancement in Eu1−xGdxO is due to Kondo-like spin fluctuations on the Gd sites, which are absent in EuO1−x. Moreover, we find that the TC saturation in Eu1−xGdxO for large x is due to a reduced activation of dopant electrons into the conduction band, in agreement with experiments, rather than antiferrom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Stoichiometric EuO has ferromagnetic transition at 69 K, but electron doping enhances the Curie temperature up to around 150 K at ambient pressure. This enhancement is a result of added charge carriers, and various mechanisms have been invoked to study its properties [11][12][13] . A recent first-principles study found that the competition between direct and indirect exchange couplings dictates many of the properties of electron doped EuO 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Stoichiometric EuO has ferromagnetic transition at 69 K, but electron doping enhances the Curie temperature up to around 150 K at ambient pressure. This enhancement is a result of added charge carriers, and various mechanisms have been invoked to study its properties [11][12][13] . A recent first-principles study found that the competition between direct and indirect exchange couplings dictates many of the properties of electron doped EuO 14 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, EuO devices were employed to for spin filtering [9][10][11][12], the interface between EuO and GdN is expected to produce a band inversion and a nonzero Chern number [13], a giant spin-phonon coupling has been reported [14], it has been suggested that a CdO/EuO superlattice is a Weyl semimetal [15], and the Hall effect of EuO thin films has been observed [16,17]. Efforts to increase the Curie temperature via doping and alloying of EuO have also seen a resurgency: Curie temperatures up to 134 K in single crystals and even higher in thin films have been achieved [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%